Outcome of biliary-enteric reconstruction with hepaticoduodenostomy following choledochal cyst resection: A prospective study - Ashok Kumar Goyal; Rahul Gupta; Neelam Meena (Wolters Kluwer Medknow Publications, 2024)
Background: The two most commonly performed methods of biliary-enteric reconstruction following choledochal cyst resection are Roux-en-Y hepaticojejunostomy (HJ) and hepaticoduodenostomy (HD). There is a lack of consensus regarding the better technique between them. This study aimed to evaluate the outcomes, efficacy and early complications of HD as a mode of biliary reconstruction after surgical resection of a choledochal cyst. Materials and Methods: This was a multi-institutional prospective study carried out in high-volume tertiary care teaching institutes from January 2010 to December 2022. All children managed with HD following choledochal cyst resection were analysed for their early complications and outcomes. Results: A total of 74 patients were included in this study. There were 59 (79.73%) females and 15 (20.27%) males. Thirty-nine (52.70%) patients had jaundice at the time of presentation. Magnetic resonance cholangiopancreatography was performed in 57 (77.03%) patients following ultrasonography. Intraoperatively, malrotation was present in 2 (2.70%) patients. In our study, operating time ranged from 60 to 195 min (mean: 118 min). Hospital stays ranged from 8 to 17 days (mean: 11.5 days). The post-operative biliary leak was seen in 7 (9.50%) patients, out of which 6 (8.11%) minor leaks were managed conservatively. Roux-en-Y HJ was performed on 1 (1.35%) patient with a major leak. In our series, 4 (5.40%) patients developed cholangitis; post-operative haemorrhagic nasogastric aspirate 5 (6.76%), post-operative pancreatitis 3 (4.05%) and wound infection 4 (5.40%) were observed and managed conservatively. None of the patients in our study developed an anastomotic stricture, bile gastritis and adhesive small bowel obstruction. Conclusion: Resection of choledochal cyst with HD reconstruction is safe and feasible with short operative time. HD is a viable option for operative management of choledochal cyst with low complication rates and faster recovery.